Case Report: H3K27M-Mutant Glioblastoma Simultaneously Present in the Brain and Long-Segment Spinal Cord Accompanied by Acute Pulmonary Embolism - Maimaiti, Buajieerguli; Mijiti, Salamaitiguli; Jiang, Ting; Xie, Yinyin; Zhao, Weixuan; Cheng, Yu; Meng, Hongmei (Frontiers in Oncology, 2022)
Background: Glioblastoma multiforme (GBM) is a highly malignant glioma that rarely presents as an infratentorial tumor. Multicentric (MC) gliomas involve lesions widely separated in space or time, and MC gliomas involving supra- and infratentorial brain regions are rare. In most cases, the infratentorial lesion is seen after surgical manipulation or radiation therapy; it is typically located in the cerebellum or the cervical region, manifesting as metastasis originating from the brain. Besides, venous thromboembolism in brain tumors is usually seen after craniotomy. Case Presentation: We present an uncommon adult case of symptomatic H3K27M-mutant MC glioblastoma simultaneously present in the brain, fourth ventricle, and cervical and lumbar spinal cord regions accompanied by acute pulmonary artery embolism in an adult woman who had not undergone previous therapeutic interventions. We also review the literature on this interesting presentation. Conclusion: Our report highlights that clinicians should be alert to the potential alarming presentation of GBM. The incidence of spinal metastasis of cerebral GBM is increasing. Patients with a prior diagnosis of GBM with or without any new onset in the spinal cord should undergo an early MRI of the spinal cord to confirm the diagnosis at an early stage. While management of GBM remains controversial, more research is needed to explore molecular features of GBM further and develop novel targeted therapies for these patients.